Process Evaluation and Experience Sharing on Utilizing Information Communication Technologies and Digital Games in a Large Community Family Health Event: Hong Kong Jockey Club SMART Family-Link Project - Shirley M. M. Sit; Agnes Y. K. Lai; Tai-on Kwok; Hoi-wa Wong; Yiu-lun Wong; Eliza Y. W. Lam; Judy Y. W. Chan; Florence S. W. Kong; Kerin Cham; Charles K. K. Ng; Teresa Yip; Terry S. Y. Tsui; et al. (Frontiers Media S.A., 2020)
Background: Information communication technologies (ICT) are increasingly used in health promotion, but integration is challenging and involves complex processes. Large community health promotion events are often held but the experiences and processes have rarely been evaluated and published. No reports have described and systematically evaluated an ICT-supported health promotion event using digital games.Objective: We evaluated the development and implementation of a large community family health promotion event with ICT integration to promote family happiness with collaboration between academia (The University of Hong Kong) and the social (family) service sector, and collected feedback from participants and social service workers.Methods: We (i) conducted a systematic process evaluation, (ii) administered an on-site questionnaire survey on participant satisfaction and feedback, and (iii) collected post-event qualitative feedback from social workers on using new technologies, digital game design and overall experiences.Results: Fourteen digital games were designed and run in booths at the event by 12 non-governmental social service organizations and academia. Four gaming technologies were utilized: chroma key (green screen), somatosensory (kinect and leap motion techniques), augmented reality and virtual reality. 1,365 participants joined the event, in which 1,257 from 454 families were recruited and pre-registered through 12 NGOs. About 39.3% were male and more than half (53.3%) were aged 18 years and above. About 3,487 game booth headcounts were recorded. Games using virtual reality, kinect motion and green screen technologies were most liked. The average game satisfaction score was high (4.5 out of 5). Social service workers reported positive experiences with using new technologies in health promotion, and interests in future collaborations involving more ICT.Conclusions: Our systematic evaluation showed successful integration of ICT components in the health promotion event. This event, most likely the first of its kind, served as a capacity building and knowledge transfer platform for interdisciplinary co-sharing and co-learning of new technologies. It provided a solid foundation for further academic and social service partnerships and should be a useful model for similar community events and their evaluation. Further development and integration of ICT for health promotion among social service organizations with comprehensive evaluation are warranted.